In Search of Lost Trams: Comparing 1925 and 2020 Transit Isochrones in Sydney - Bahman Lahoorpoor; David Levinson (Findings)
Has Sydney lost access by removing its extensive tram network? We compare the 1925 tram network with today's bus network, and conclude that the access provided today exceeds what would have been provided by just trams. The Sydney CBD would have had better access if 1925's central tram lines were still in operation.